Health insurance system and provider payment reform in the Republic of Macedonia (Italian Journal of Public Health, 2009)
This article gives an insight to the current health insurance system in the Republic of Macedonia. Specialemphasis is given to the specificities and practice of both obligatory and voluntary health insurance, to thescope of the insured persons and their benefits and obligations, the way of calculating and payment of thecontributions and the other sources of revenues for health insurance, user participation in health careexpenses, payment to the health care providers and some other aspects of realization of health insurance inpractice. According to the Health Insurance Law, which was adopted in March 2000, a person can become aninsured to the Health Insurance Fund on various modalities. More than 90% of the citizens are eligible to theobligatory health insurance, which provides a broad scope of basic health care benefits. Till end of 2008payroll contributions were equal to 9.2%, and from January 1st, 2009 are equal to 7.5% of gross earned wagesand almost 60% of health sector revenues are derived from them. Within the autonomy and scope of activitiesof the Health Insurance Fund the structures of the revenues and expenditures are presented. Health financingand reform of the payment to health care providers are of high importance within the ongoing health carereform in Macedonia. It is expected that the newly introduced methods of payments at the primary health carelevel (capitation) and at the hospital sector (global budgeting, DRGs) will lead to increased equity, efficiencyand quality of health care in hospitals and overall system.
Keywords: health insurance system; Republic of Macedonia (FYR); provider payment reform; capitation; global budgeting; DRGs